Two rare and interesting species of Pezizales (fungi) from Bosnia and Herzegovina - Peziza montirivicola and Trichophaea flavobrunnea - Nedim Jukić (Glasnik Šumarskog Fakulteta Univerziteta u Banjoj Luci)
Two interesting and rarely occurring species of fungi from the order Pezizales found in Bosnia and Herzegovina are presented here. Ecology, morphology, microscopic characters and conservation status of Peziza montirivicola and Trichophaea flavobrunnea are briefly discussed in the paper. Notes on the similar species of operculate discomycetes are given.